Analisis Efisiensi Dan Efektivitas Penerimaan Pendapatan Asli Daerah Kabupaten Klungkung - julastiana, yaneka (E-Jurnal Akuntansi, 2012)
The purpose of this study was to analyze the efficiency and effectiveness of tax revenue and levies to revenue in 2005-2011 Klungkung regency. Analysis of the data used is quantitative analysis by measuring the efficiency and effectiveness of the management of taxes and levies on revenues Revenue Klungkung regency years 2005-2011. The results of the analysis of the data shows, the level of efficiency of taxes and retributions Klungkung regency quite efficient in 2005-2011 an average of 70.97 percent. Rate the effectiveness of the tax revenue and levies Klungkung regency years 2005-2011 are considered very effective average rate of 112.36 percent.
Keywords: efficiency, effectiveness, taxes and levies